1990
DOI: 10.1002/adv.1990.060100104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oscillations during extrusion on rheology and mechanical properties of polymers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
63
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 17 publications
0
63
0
Order By: Relevance
“…Isayev et al 21,22 reported that during extrusion a high-intensity ultrasonic vibration could reduce die pressure and extrudate swelling as well as postpone melt fracture. In our previous work, ultrasonic vibration technology was developed to improve the processability of ultrahigh-molecular-weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%
“…Isayev et al 21,22 reported that during extrusion a high-intensity ultrasonic vibration could reduce die pressure and extrudate swelling as well as postpone melt fracture. In our previous work, ultrasonic vibration technology was developed to improve the processability of ultrahigh-molecular-weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%
“…20,24 It has been found that vibration affects diffusion and rate-sensitive processes 24 such as crystallization dynamics 25 and blending. 26 In polymer processing, many prospective vibration technologies such as ultrasonic vibration 27 or mechanical vibration 27,28 have been used. A detailed review on various vibration technologies is given by Ibar.…”
mentioning
confidence: 99%
“…33 At present, Haake, Brookfield, Brabander, Cotraves, and other types of small-scale internal mixers are used in labs to simulate the practical processes of polymer processing conveniently, the great differences of which lie in the controlling kernel parts. It is worth mentioning that mechanical vibration has been introduced in injection 24,27,34 as well as in the singlescrew extrusion. 27,28,35 However, there have been few reports on the application of vibration in the twin-screw extruder probably because of its complex structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we developed the ultrasonic injection molding (UIM) system. Numerous studies have been investigated polymer processing using ultrasonic waves [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, except for the application of such vibration at a low frequency range [18,19], few such reports describe the application of ultrasonic vibration to injection molding.…”
Section: Introductionmentioning
confidence: 99%